NATIONAL SECURITY AND BORDER MANAGEMENT IN WEST AFRICA: A STUDY OF NIGERIA-NIGER RELATIONS - IYANU-OLUWA AYOBAMI AYODELE; UMARU TOYIN SHIRU (International Studies Journal)
National Security and Border Management in West Africa is an important discourse in security studies in a time when high insecurity and other crimes such as terrorism, kidnapping, arms and weapons smuggling are pervasive. This paper seeks to outline the benefit of a good national security and adequate management strategy to the internal security of states. National security challenges in West African countries partly stem from ineffective border management strategies. Borders between states are porous, unsafe and this allows the illegal movement of people mostly allowing increased insecurity such as terrorism, smuggling, kidnapping, human trafficking and proliferation of arms and small weapons. This paper would rely majorly on secondary sources analyzing already existing documents and works on the subject matter. National security cannot be guaranteed without a proper border management strategy put in place by both Nigeria and Niger as most issues arise from poor border management.  This paper intends to contribute to knowledge by arguing that Nigeria-Niger relations particularly border management is critical to the protection of the territorial integrity of the states from the activities of violent non-state actor. The efforts of the states can be impeded based on the ECOWAS Protocol on Free Movement of Goods and Persons which will not allow restriction of people in and out of ECOWAS region.  This paper also interrogates the recent withdrawal of Niger from ECOWAS and MNJTF and its implications to Nigeria-Niger security arrangement particularly with the presence of various security threats common to both states. Nigeria requires Niger continuous security/military cooperation to ensure its national security is not breached around the border region.